The factors influencing the changes of deposit in Islamic bank Malaysia and Indonesia / Nurul Assyira Luqman Alhakim - Luqman Alhakim, Nurul Assyira (2022)
The purpose of this research is to look at the factors that influence deposit changes in Islamic banks in the context of a Malaysia-Indonesia study. The mudharabah deposits are the subject of this article. It has been discovered that four variables are being evaluated in relation to this issue which are bank reserve, non-performing financing, rate of return and interest rate. The data for this research came from a variety of bank-related databases and annual reports. This study used secondary data from ten (10) selected Islamic banks in Malaysia and Indonesia from 2015 to 2019. The obtained data is investigated using panel data in this study. Descriptive analysis, correlation analysis, regression analysis, and normality analysis are all used to explain the findings in this study.